Intervención educativa y su efecto en las prácticas preventivas sobre dengue en pobladores del asentamiento humano Manuel Cardozo Iquitos 2023 - Rodriguez Lecca, Saskya Alessandra (2025)
The objective of the study was to determine the effect of the educational intervention on preventive practices on Dengue in residents aged 18 to 75 years of the Manuel Cardozo Dávila Human Settlement, Iquitos 2023. The method was quantitative with a quasi-experimental design, a sample of 30 was included participants, the techniques were observation, home visit, educational session and demonstration session, the instruments were the checklist (Validity 95.14% and reliability 93%) and the educational intervention program. The results were: Before the educational intervention, 93.3% of the participants carried out inadequate preventive practices on Dengue, while only 6.7% carried out adequate preventive practices. After the intervention, 90% carried out adequate preventive practices on Dengue, while only 10% carried out inappropriate preventive practices. The educational intervention improved preventive practices on Dengue in residents aged 18 and 75 years of the Manuel Cardozo Dávila Human Settlement (p <0.001). The work concludes that the educational intervention was effective in preventive practices on Dengue.